Assessing the Influence of Artificial Intelligence Tools on Personalized Reading Practices at IAIN Palopo and Universitas Negeri Makassar - Wisran Wisran; Muh. Safar Nur; Auliyanti Sahril Nurfadhilah; Nina Ariani (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
This study investigates the impact of Artificial Intelligence (AI) tools on improving reading comprehension, vocabulary acquisition, and reading fluency among IAIN Palopo and Universitas Negeri Makassar students. With the increasing integration of AI in educational settings, this research aims to assess how personalized learning environments provided by AI can enhance students' literacy skills. A mixed-methods approach was employed, combining quantitative data from pre-and post-test scores with qualitative data from student and lecturer interviews. The results indicate significant improvements in reading comprehension, vocabulary acquisition, and reading fluency, with moderate to large effect sizes observed across both institutions. Additionally, qualitative findings reveal that AI tools motivated students, increased engagement, and provided personalized learning experiences. However, challenges such as technological access and infrastructure limitations were identified, particularly at Universitas Negeri Makassar, which affected students’ ability to engage with the tools fully. The study concludes that while AI tools can significantly improve reading skills, successful implementation requires addressing infrastructure issues and ensuring the cultural relevance of learning materials. The findings suggest that AI should complement traditional pedagogical practices rather than replace them, offering a blended learning approach that supports deeper learning. This research contributes to the growing body of knowledge on AI in education and highlights the importance of adapting AI tools to local contexts to maximize their effectiveness.